ANALISIS PENGELOLAAN UTANG PT. TIRTA MAHAKAM RESOURCES,TBK PERIODE 2011 – 2013 - RINA MASITHOH HARYADI, YENY PUJI ASTUTI. TITIN RULIANA. (EKONOMIA, 2016)
In general, companies use their own capital as the permanent capital of the foreign capital is only used as a supplement if the necessary funding is insufficient. However, debt is a very important source of funding for companies, particularly those with limited capital itself. Many companies in Indonesia that make loans to Banks and other financial institutions. PT. Tirta Mahakam Resources, Tbk is one of the companies that use foreign capital (debt). Based on this background, the problems in this thesis is "Does the increase fixed assets financed by debt in period 2011 - 2013?". Purpose of this study was to determine the development of fixed assets financed from debt in the period 2011 - 2013, by analyzing the financial statements PT.Tirta Mahakam Resources, Tbk in 2011, 2012, and 2013, as measured using a solvency ratio comprises Assets of the Capital Ratio, with a Capital Ratio of Fixed Assets, Fixed Assets Ratio with long-termdebt.Analysis and discussion of the results showed that a decline in fixed assets financed by debt in the period in 2011, 2012, and 2013 as measured by the ratio of capital to assets, with a Capital Ratio of Fixed Assets, Fixed Assets Ratio with long-term debt. Capital to assets ratio in 2011 shows the figure of 0.19%, 0.15% in 2012 and by 2013 at 0:08%. Capital to Assets Ratio of 2011 showed a figure of 0.73%, 2012 0:55% and in 2013 of 0:18%. The ratio of fixed assets with long-term debt in 2011 shows the figure of 0.91%, 2012 1:15% and in 2013 at 1:26%. Based on the conclusions that have been submitted then the hypothesis There is an increase fixed assets financed by debt in the period 2011 â€“ 2013 increased, rejected.Â